Air-stable bismuth sulfobromide (BiSBr) visible-light absorbers: optoelectronic properties and potential for energy harvesting - Guo, X; Huang, YT; Lohan, H; Ye, J; Lin, Y; Lim, J; Gauriot, N; Zelewski, SJ; Darvill, D; Zhu, H; Rao, A; McCulloch, I; et al. (Royal Society of Chemistry, 2023)
ns2 compounds have recently attracted considerable interest due to their potential to replicate the defect tolerance of lead-halide perovskites and overcome their toxicity and stability limitations. However, only a handful of compounds beyond the perovskite family have been explored thus far. Herein, we investigate bismuth sulfobromide (BiSBr), which is a quasi-one-dimensional semiconductor, but very little is known about its optoelectronic properties or how it can be processed as thin films. We develop a solution processing route to achieve phase-pure, stoichiometric BiSBr films (ca. 240 nm thick), which we show to be stable in ambient air for over two weeks without encapsulation. The bandgap (1.91 ± 0.06 eV) is ideal for harvesting visible light from common indoor light sources, and we calculate the optical limit in efficiency (i.e., spectroscopic limited maximum efficiency, SLME) to be 43.6% under 1000 lux white light emitting diode illumination. The photoluminescence lifetime is also found to exceed the 1 ns threshold for photovoltaic absorber materials worth further development. Through X-ray photoemission spectroscopy and Kelvin probe measurements, we find the BiSBr films grown to be n-type, with an electron affinity of 4.1 ± 0.1 eV and ionization potential of 6.0 ± 0.1 eV, which are compatible with a wide range of established charge transport layer materials. This work shows BiSBr to hold promise for indoor photovoltaics, as well as other visible-light harvesting applications, such as photoelectrochemical cells, or top-cells for tandem photovoltaics.